Analisis Pengaruh Harga, Kualitas Produk dan Promosi Terhadap Pengambilan Keputusan Pembelian Toyota Avanza(Studi kasus pada pt. Nasmoco solo baru) - Prasetiyo, Bundan Rachmad, Drs.Sri Padmantyo,MBA (2017)
The purpose of this study is to determine the effect of pricing, product quality, and promotion of the purchasing decision of Toyota Avanza in PT Nasmoco Solo Baru. The sampling technique used was accidental sampling, samples are 50 respondents, while an analysis tool used is multiple linear regression, t-test, F, and keofisien determination (R2).Based on the results of this research note coefficient of determination (R2) = 0.417 can be said that the 41.7% price variable (X1), product quality (X2), and promotion (X3) influence on purchase decisions (Y), while the remaining 58, 3% are caused by other variables not included in this study. F test results obtained calculated F value of 12.665 while the F table at significant level of 5% was 2.81, it turns out F count larger than F table then Ho or the null hypothesis is rejected and the conclusions drawn price variable (X1), product quality (X2) and promotion (X3) have significant influence jointly on purchase decisions (Y).